PENGARUH CITRA MEREK DAN KUALITAS PRODUK MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING TERHADAP LOYALITAS PELANGGAN PADA PRODUK INDOMIE (Studi pada Mahasiswa Perguruan Tinggi Negeri di Surabaya) - Lilik Indra Mulyana; Lisa Sulistyawati (Universitas Halu Oleo, 2022)
This research aims to find out the effect of brand image and product quality on customer’s loyalty directly and indirectly through the customer satisfaction. This research itself uses Indomie as the product object. Along with it, this research’s populations are all the customers who have bought or consumed the product itself. In addition, there are total of 100 respondents consist of customers from the Indomie product used as the sample of the research. All those samples were obtained by using the non-probability sampling technique together with quota sampling as its method. The hypothetical testing in this research uses the statistical model analysis that includes validity tests, reliability test, classical assumption test, path analysis, T test, and sobel test. Therefore, the result of this research shows that brand image has a significant effect customer satisfaction. Product quality has a significant effect on customer satisfaction. Brand image has no significant effect on customer loyalty. Product quality has a significant effect on customer loyalty. Customer satisfaction has a significant effect on customer loyalty. Brand image has a significant effect on customer loyalty through customer satisfaction. Product quality has a significant effect on customer loyalty through customer satisfaction.